2021
DOI: 10.1186/s13020-021-00543-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of drug-induced liver injury and hepatoprotective effects of natural drugs

Abstract: Drug-induced liver injury (DILI) is a common adverse drug reaction (ADR) and a serious threat to health that affects disease treatments. At present, no targeted clinical drugs are available for DILI. Traditional natural medicines have been widely used as health products. Some natural medicines exert specific hepatoprotective effects, with few side effects and significant clinical efficacy. Thus, natural medicines may be a promising direction for DILI treatment. In this review, we summarize the current knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 181 publications
0
13
0
Order By: Relevance
“…Natural products are a treasure trove of drugs worth developing and utilizing. In the future, investigating new drugs using natural products as the source will be one of the critical approaches for AILI treatment (Zhou et al, 2021). The various components of natural medicines provide multiple targets for disease treatment.…”
Section: Management Of Ailimentioning
confidence: 99%
“…Natural products are a treasure trove of drugs worth developing and utilizing. In the future, investigating new drugs using natural products as the source will be one of the critical approaches for AILI treatment (Zhou et al, 2021). The various components of natural medicines provide multiple targets for disease treatment.…”
Section: Management Of Ailimentioning
confidence: 99%
“…DILI accounts for 10% of all hepatitis cases and is the leading cause of acute liver failure in the USA [ 16 ]. Recent studies have shown that certain drugs are associated with DILI [ 17 ]. 5-ASA is generally considered a safe drug with few side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Natural medicines containing flavonoids and other functional components, particularly polyphenols, are increasingly used in clinical therapy [ 52 ]. In the elderly population with chronic diseases such as hypertension, hyperlipidemia [ 53 ], and hyperuricemia, it is common to use prescription drugs, over-the-counter drugs, and natural products simultaneously [ 47 , 54 ].…”
Section: Oat3 and Herb–drug Interactions (Hdis)mentioning
confidence: 99%